2017
DOI: 10.1371/journal.pone.0179307
|View full text |Cite
|
Sign up to set email alerts
|

Is normal-tension glaucoma a risk factor for stroke?—A 10-year follow-up study

Abstract: ObjectivesTo investigate whether patients with normal-tension glaucoma (NTG) have a higher incidence of stroke.DesignA population-based retrospective cohort study based on data from the Taiwan National Health Insurance Research Database (NHIRD) from January 1, 2001, to December 31, 2010.MethodsData were retrospectively collected from the NHIRD. A total of 245 (20.1%) patients with a history of stroke at the time of glaucoma diagnosis were excluded, and 1,218 patients with NTG who were 20 years of age and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Meta-regression also failed to distinguish the exact source of the heterogeneity. Several factors, such as different characteristics of the populations, different quality of the included studies, different methods used to ascertain outcomes and exposure, different sample 44 Age, sex Chen (2005) 9 Age, SBP, DBP, glucose Motsko (2008) 54 Age, sex Lin (2010) 8 Age, gender, monthly income, and level of urbanization of the community in which the patient resided Lin (2010) 45 Age, sex Imai (2010) 42 Age, maximum temperature, increased abdominal circumference, elevated fasting glucose level, BP Ishikawa (2011) 52 Age, sex, DBP, IOP, and ocular perfusion pressure Newman-Casey (2011) 7 Age, sex, race, education level, household net worth, region of residence at the time of enrollment in the medical plan, cataract, pseudophakia or aphakia, macular degeneration, diabetic retinopathy, systemic hypotension, sleep apnea, and migraine headache Lee (2012) 46 Age, sex, SBP Lin (2012) 33 Age, sex, BMI, waist, SBP, DBP, fasting sugar, and postprandial sugar Kim (2014) 34 Age, sex, impaired glucose tolerance, hypertension, and baseline IOP Aptel (2014) 47 Age, sex, BMI, hypertension, and thyroid dysfunction Kim (2014) 43 Age, sex Chung (2014) 53 Age, sex Kim (2014) 55 Age, sex, myopia, fasting blood glucose Chen (2014) 48 Age, sex, hypertension, diabetes, CAD, and obstructive sleep apnea Sahinoglu-Keskek (2014) 41 Age Fujiwara (2015) 49 Age, sex, SBP, diabetes, cholesterol, HDLcholesterol, BMI, waist circumference, smoking habits, alcohol intake, and regular exercise Shim (2015) 32 Age, sex Chen (2016) 50 Age, sex Chen (2016) 51 Age, gender, and comorbidities of diabetes, hypertension, and CAD Ko (2016) 35 Age, gender, ethnicity, education, insurance, diabetes duration, BMI, hypertension, obstructive sleep apnea, and current smoker Kim (2016) 36 Age, sex, IOP, household income, exercise, education level, smoking status, alcohol consumption, and BMI Yokomichi (2016) 10 Age, sex, SBP, DBP, fasting plasma glucose Rim (2017) 37 Age, sex, hypertension, DM, chronic renal failure, atrial fibrillation, residence, income Lee (2017) 38 Age, sex, hypertension, DM, congestive heart failure, ischemic heart disease, atrial fibrillat...…”
Section: Discussionmentioning
confidence: 99%
“…Meta-regression also failed to distinguish the exact source of the heterogeneity. Several factors, such as different characteristics of the populations, different quality of the included studies, different methods used to ascertain outcomes and exposure, different sample 44 Age, sex Chen (2005) 9 Age, SBP, DBP, glucose Motsko (2008) 54 Age, sex Lin (2010) 8 Age, gender, monthly income, and level of urbanization of the community in which the patient resided Lin (2010) 45 Age, sex Imai (2010) 42 Age, maximum temperature, increased abdominal circumference, elevated fasting glucose level, BP Ishikawa (2011) 52 Age, sex, DBP, IOP, and ocular perfusion pressure Newman-Casey (2011) 7 Age, sex, race, education level, household net worth, region of residence at the time of enrollment in the medical plan, cataract, pseudophakia or aphakia, macular degeneration, diabetic retinopathy, systemic hypotension, sleep apnea, and migraine headache Lee (2012) 46 Age, sex, SBP Lin (2012) 33 Age, sex, BMI, waist, SBP, DBP, fasting sugar, and postprandial sugar Kim (2014) 34 Age, sex, impaired glucose tolerance, hypertension, and baseline IOP Aptel (2014) 47 Age, sex, BMI, hypertension, and thyroid dysfunction Kim (2014) 43 Age, sex Chung (2014) 53 Age, sex Kim (2014) 55 Age, sex, myopia, fasting blood glucose Chen (2014) 48 Age, sex, hypertension, diabetes, CAD, and obstructive sleep apnea Sahinoglu-Keskek (2014) 41 Age Fujiwara (2015) 49 Age, sex, SBP, diabetes, cholesterol, HDLcholesterol, BMI, waist circumference, smoking habits, alcohol intake, and regular exercise Shim (2015) 32 Age, sex Chen (2016) 50 Age, sex Chen (2016) 51 Age, gender, and comorbidities of diabetes, hypertension, and CAD Ko (2016) 35 Age, gender, ethnicity, education, insurance, diabetes duration, BMI, hypertension, obstructive sleep apnea, and current smoker Kim (2016) 36 Age, sex, IOP, household income, exercise, education level, smoking status, alcohol consumption, and BMI Yokomichi (2016) 10 Age, sex, SBP, DBP, fasting plasma glucose Rim (2017) 37 Age, sex, hypertension, DM, chronic renal failure, atrial fibrillation, residence, income Lee (2017) 38 Age, sex, hypertension, DM, congestive heart failure, ischemic heart disease, atrial fibrillat...…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the diagnostic prevalence of glaucoma in the younger age categories was almost the same as that in the older age categories. One reason is that the prevalence of open-angle glaucoma (including normal tension glaucoma) has been higher than that of angle-closure glaucoma since 2005 [ 21 ], and patients with normal tension glaucoma generally have a younger age than those with angle-closure glaucoma [ 22 ], thus lowering the average age of glaucoma patients. Another reason is the high accessibility of healthcare achieved by the Taiwan NHI system [ 23 ], thus glaucoma can be diagnosed at an earlier age.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular disease plays a critical role in the pathogenesis of glaucoma 28 and is more frequent in patients with NTG than in patients with HTG or healthy subjects. 29 Thus, our prospective clinical research provides evidence of cerebrovascular dysfunction in patients with NTG. Recent studies have shown reduced cerebrovascular blood flow velocities 30 , 31 and increased risk of Alzheimer disease or other dementia in patients with NTG.…”
Section: Discussionmentioning
confidence: 86%